Synthesis of Bacteriostatic Materials from Quaternary Ammonium Salts - Tahsin, Kazi Naziba (CMBES Proceedings, 2024)
Dental implants are commonly used to address tooth loss. Since the implant's surface is exposed to the oral cavity, it becomes susceptible to colonization by microorganisms. Recent in vivo research demonstrated that bacterial colonization begins as early as 30 minutes after implant placement. The most common bacteria associated with dental implant infections include Staphylococcus aureus. Engineering the implant surface to provide antimicrobial activity is one line of defence that has been taken up in recent years. An antimicrobial coating was prepared by quaternising the copolymer of vinylbenzyl chloride (VBC) and [3-(Methacryloyloxy)propyl]trimethoxysilane (MPS). The copolymer MPS-VBC was synthesized by free radical polymerization. The obtained copolymer was then quaternized to form Quaternized Salts (QAS) which were characterized by Fourier Transform Infrared (FTIR). The baceriostatic property of these compounds was investigated in gram positive, S. Aureus, by serial dilution method. This work explores the development and application of a novel quaternary ammonium, attached to economical and clinically relevant material surfaces.